Road traffic injuries and fatalities among drivers distracted by mobile devices - Natasa Zatezalo (Journal of Emergencies, Trauma and Shock, 2018)
Context: With increasing ownership of mobile devices (i.e., cell phones and smartphones), it is important to better understand the role of these devices in motor vehicle collision (MVC)-related trauma. Aims: The primary objective was to synthesize evidence on the proportion of drivers injured or killed in an MVC attributed to driver distraction by a mobile device. As a secondary objective, we assessed for associations between injury risk and mobile device use while driving. Settings and Design: This study was a systematic review. Subjects and Methods: We searched five electronic databases (PubMed, Embase, CINAHL, TRIS, and Web of Science) and the gray literature to identify reports of drivers injured (regardless of the severity) or killed in MVCs attributed to mobile device-related distraction by the driver. We evaluated study and driver characteristics, as well as associations between injury risk and mobile device use by drivers. Statistical Analysis Used: Descriptive statistics were used to report study characteristics. The proportion of injuries related to driver distraction by mobile devices was calculated for each study. Results: Overall, 4907 articles were screened, of which 13 met eligibility criteria. The median proportion of distracted-driving-related trauma was 3.4% (range: 0.04% to 44.7%). Three studies evaluated the association between mobile device use and road traffic injury; all found use of a mobile device while driving significantly increased crash risk. Conclusions: The proportion of road traffic injuries and fatalities attributed to driver distraction by a mobile device ranges from 0.04% to 44.7%. Studies were subject to limitations in the collection of reliable data on distraction-related MVCs.